PUNJAB'S TOURISM POLICY IN FOCUS: AN IN-DEPTH ANALYSIS - Pervez, Zahid (Public Policy Journal, 2023)
The tourism industry has gained immense popularity in the 21st century and for many developed and developing countries owing to its socio-economic dividends. Tourism requires systematic planning for its development. The purpose of tourism planning is to efficiently manage the supply and demand of tourism in the area. Tourism policies are formulated to include tourism planning to increase tourism in the country. This policy paper analyzes the Punjab Tourism Policy, 2019. The Punjab Tourism Policy 2019 was formed with a view to providing a holistic and cross-cutting framework for strengthening the tourism infrastructure and improving governance and regulation regime. The policy aimed at promoting a soft image of the province and Pakistan and attracting more foreign as well as local tourists for overall economic uplift and well-being of communities. The review of the policy and analysis of the available information and data shows that considerable progress has been made in the tourism sector of Punjab. There has been some investment in the physical infrastructure of existing sites and new attractions have been identified and development started. A separate Department of Tourism and Archeology has been created and subordinate organizations like TDCP, DTS, etc. are being revitalized. Moreover, various steps including but not limited to outsourcing of resorts by TDCP, and installation of safety measures such as Punjab Tourism Squad by DTS, have been initiated. Despite significant progress, various factors have hindered the achievement of set goals owing to political, administrative, and financial factors. It is high time that the government took stock of the situation by mid-course review of the policy to remove bottlenecks that hinder the realization of the full potential of the tourism sector.